A model chain approach for coastal inundation: Application to the bay of Alghero. (5th April 2019) - Postacchini, Matteo; Lalli, Francesco; Memmola, Francesco; Bruschi, Antonello; Bellafiore, Debora; Lisi, Iolanda; Zitti, Gianluca; Brocchini, Maurizio
Abstract: Coastal inundation is an important threat for many nearshore regions worldwide, and has significantly increased in the last years also due to sea-level rise and augmented impact of extreme events, like sea storms. Many countries and regions have recently invested to overcome such problems, which commonly lead to structure damages, beach erosion and many other consequences. Numerical modeling is an important tool for coastal inundation prediction, being a valuable support for management issues to mitigate the inundation risk or suggest resilient solutions. The present work illustrates a novel approach, based on a numerical model chain that exploits a tide-surge-wave operational modeling system (Kassandra), a phase-averaged model (ROMS-SWAN) for the wave propagation towards the shore, and a phase-resolving solver (NSWE) for the prediction of runup and coastal inundation. Such a chain is applied to the bay of Alghero (Sardinia, Italy), where the results of the mentioned chain are compared to those obtained using, in place of the phase-averaged model, an analytical model for the wave propagation. Results confirm that both chain approaches provide comparable inundations, though the use of the analytical, more approximate (e.g., less accurate and reliable description of wave breaking dissipation), model suggests more severe conditions and larger flooded areas. Our contribution provides a methodological approach for an accurate and reliable estimate of coastal flooding. Highlights: Coastal inundation intensified in the last years also due to increase of extremes. Regulations have been proposed worldwide to mitigate effects of coastal inundation. A model chain is proposed for the wave propagation from deep waters to the coast. The proposed methodology enables prediction of runup and coastal inundation. The modeling chain is applied to the bay of Alghero (Sardinia, Italy).